Pola Motivasi Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di Madrasah Ibtidaiyah Al-Jam’iyatul Washliyah Murtajih Pademawu Pamekasan - atnawi, atnawi (Fakultas Agama Islam Universitas Islam Madura, 2019)
This study is Aimed at the main three purposes: (1) How does the pattern of principal motivation in improving teacher performance in MI Al-Jam'iyatul Washliyah Murtajih Pademawu Pamekasan; (2) How is the performance of teachers in MI Al-Jam'iyatul Washliyah Murtajih Pademawu Pamekasan; (3) What are the factors supporting and inhibiting principal in improving teacher performance in MI Al-Jam'iyatul Washliyah Murtajih Pademawu Pamekasan. This study used a qualitative approach with descriptive. Source of data obtained through interviews, observation and documentation. Informant is the principal and the teachers. While checking the validity of the data is done through observation extension, increased diligence in research, triangulation, peer discussions, negative case analysis and member-check. The results showed that: first, principal has performed well pattern motivation to teachers. The pattern is a pattern applied motivation intrinsic motivation and in its implementation using a democratic leadership. The pattern shown motivation to teachers is: involve teachers in any of the activities carried out in schools, giving awards to teachers, especially for teachers who demonstrate good performance, creating an atmosphere of work space, a library, and a comfortable setting school environment, safe and fun and imposing sanctions if there are teachers who violate the discipline that has been agreed. Second, the performance is quite good teachers, because teachers in implementing the tasks and obligations showed high performance, such as teaching in a timely, organized preparations to teach well, providing guidance to the students' difficulties, whether requested or not requested. To determine the performance of good teachers, principals, especially assessment of the learning process as the main program that has been set. Third, the factors that supports the democratic leadership, fostering discipline, generating motivation and giving awards to teachers who excel. Meanwhile, the limiting factor is the lack of discipline principals, facilities and inadequate infrastructure, lack of training for teachers who are less professional, and lack of teacher salaries lead teacher performance decreases.